The Semiology of Narrative Construction in Television Advertising to an Announce "God Will not Forget us" about the Covid-19 Pandemic for Zain Mobile Telecommunication Company - Al-Azzawi, Muhammed Mahmood; Jameel, Bushra (ALBAHITH ALALAMI, 2021)
This research paper tries to show the significance of the narrative structure in the television advertisement and its connotations. The researchers chose the annual advertisement of Zain Mobile Telecommunication Company for the year 2020, which shed light on the global Corona pandemic crisis. The idea of the advertisement won wide approval as it focused on the suffering that everyone is witnessing like medical and security personnel in particular, and family relationships consequences.In addition to the positive global interaction with the message presented by the Company in these exceptional circumstances. The advertisement, which lasted for 2.35 minutes, exceeded 13 million views in a short period of time. This prompted us to choose this advertisement to find out the importance and truth of the role entrusted with advertisements of social responsibility for service companies in facing epidemics and diseases and raising awareness about those epidemics and diseases.